Biodegradable Covalently Crosslinked Poly[N-(2-Hydroxypropyl) Methacrylamide] Nanogels: Preparation and Physicochemical Properties - Kousalová, Jana; Šálek, Petr; Pavlova, Ewa; Konefał, Rafał; Kobera, Libor; Brus, Jiří; Kočková, Olga; Etrych, Tomáš (Polymers, 2024)
Recently, suitably sized polymer-based nanogels containing functional groups for the binding of biologically active substances and ultimately degradable to products that can be removed by glomerular filtration have become extensively studied systems in the field of drug delivery. Herein, we designed and tailored the synthesis of hydrophilic and biodegradable poly[N-(2-hydroxypropyl) methacrylamide-co-N,N'-bis(acryloyl) cystamine-co-6-methacrylamidohexanoyl hydrazine] (PHPMA-BAC-BMH) nanogels. The facile and versatile dispersion polymerization enabled the preparation of nanogels with a diameter below 50 nm, which is the key parameter for efficient and selective passive tumor targeting. The effects of the N,N'-bis(acryloyl) cystamine crosslinker, polymerization composition, and medium including H2O/MetCel and H2O/EtCel on the particle size, particle size distribution, morphology, and polymerization kinetics and copolymer composition were investigated in detail. We demonstrated the formation of a 38 nm colloidally stable PHPMA-BAC-BMH nanogel with a core-shell structure that can be rapidly degraded in the presence of 10 mM glutathione solution under physiologic conditions. The nanogels were stable in an aqueous solution modeling the bloodstream; thus, these nanogels have the potential to become highly important carriers in the drug delivery of various molecules.
Keywords: nanogel; dispersion polymerization; glutathione; biodegradable; N-(2-hydroxypropyl) methacrylamide